ZMIENN OŚĆ CZASOWA I ZRÓŻNICOWANIE PRZESTRZENN E ZACHM URZENIA W POLSCE W LATACH 2001–2016 - Sypniewska, Ligia; Szyga–Pluta, Katarzyna (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The study presents the characteristic of annual, seasonal and diurnal course of cloudiness in Poland in 2001–2016. The analysis was performed on 28 meteorological stations (IMGW-PIB); the data came from threefold climatological observations. Based on the data, the average course of annual, seasonal and diurnal cloud cover, maximum and minimum values were estimated. Moreover, the average number of characteristic nephological days during the year was calculated. The analysis confirmed a decrease in cloudiness in the spring and in the summer accompanied by an increase in the autumn and in the winter season. Furthermore, in the summer the values of diurnal cloud variation were higher in the summer than in the winter. August was the least cloudy month (56%) while December proved most cloudy (79%). During the entire period in question, the Pomeranian Lakeland was most clouded while the Szczecin Shore Zone proved the least cloudy.